Surgical treatment for atlantoaxial rotatory fixation in an adult with spastic torticollis: A case report. (May 2020) - Akiyama, Yuki; Takahashi, Hiroshi; Saito, Junya; Aoki, Yasuchika; Nakajima, Arata; Sonobe, Masato; Akatsu, Yorikazu; Yamada, Manabu; Yanagisawa, Keita; Shiga, Yasuhiro; Inage, Kazuhide; Orita, Sumihisa; et al.
Highlights: We report a case of atlantoaxial rotatory fixation in an adult with spastic torticollis. Surgical treatment for atlantoaxial rotatory fixation in an adult should be considered if the diagnosis is delayed. The possibility of revealing spastic torticollis after existing AARF surgery should be considered. Appropriate treatment for spastic torticollis applied after surgery resulted in a favorable outcome. Abstract: Atlantoaxial rotatory fixation (AARF) in an adult without any trauma is an extremely rare condition. Here we report a case of surgical treatment for existing atlantoaxial rotatory fixation in an adult with spastic torticollis. A 50-year-old man had become aware of torticollis without any cause of injury 6 weeks before he visited our hospital, where he presented with a one-week history of severe neck pain. Based on the local and imaging findings, we diagnosed him as having existing AARF of Fielding classification type I. The AARF was not reduced by 3 weeks of Glisson traction. Thus, we performed C1–C2 posterior fusion surgery 3 months after his initial visit. Although CT findings just after surgery showed that the C1-2 facet subluxation was reduced, the complaint of torticollis was not improved, with scoliosis at the middle to lower cervical level because of left sternocleidomastoid hypertonia. Administration of diazepam was initiated 2 weeks after surgery and botulinum toxin injections to the left sternocleidomastoid were added 2 months after surgery under the neurological diagnosis of spastic torticollis. As a result, the complaint of his torticollis was significantly improved 3 months after surgery. There were no relapses of the torticollis and complete fusion of the C1–C2 laminae was observed at the 2-year final follow-up. Surgical treatment for AARF in an adult should be considered if the diagnosis of AARF is delayed. In addition, appropriate treatment for spastic torticollis applied after surgery resulted in a favorable outcome of this case.